Enhance health evidence quality in classification tasks: A triangulation approach utilizing case-based reasoning and process features - Ruihua Guo; Ross Smith; Qifan Chen; Angus Ritchie; Simon Poon (Digital Health)
Objective Machine learning (ML) has enabled healthcare discoveries by facilitating efficient modeling, such as for cancer screening. Unlike clinical trials, real-world data used in ML are often gathered for multiple purposes, leading to bias and missing information for a specific classification task. This challenge is especially pronounced in healthcare because of stringent ethical considerations and resource constraints. This study proposed an integrated approach to enhance the quality of health evidence from a classification task for predicting Medicare's Diagnosis-Related Groups of ischemic heart disease (IHD) patients. Methods Eligible participants were identified from the Medical Information Mart for Intensive Care IV (MIMIC IV), a publicly available hospital database. Six ML models were selected for model triangulation. Sequential triangulation was employed via Local Process Mining (LPM) and Qualitative Comparative Analysis (QCA). Results A total of 1545 IHD hospitalizations from 916 patients were identified from the MIMIC IV. Eight health process features were identified through LPM aligned with clinical knowledge. The correlation coefficients for process features, ranging from 0.24 to 0.42, are higher than those for non-process features ranged from 0.02 to 0.36. A total of 56 unique combinations were identified from the QCA, with 28 configurations having raw coverage lower than 1.0%. The overall model performance (i.e. weighted F1 and area under the curve scores) increased after adopting this integrated approach. The proportion of cases misclassified by any of the six models decreased by 47% after incorporating process features (from 5.29% to 2.91%) and further decreased to 0.0% after applying the QCA solutions. Conclusion The integrated approach demonstrates its ability to enhance quality of a classification task through its clinical relevance, improved model performance, and reduced case-level error rates. However, more scalable QCA methods are needed for larger datasets. Developing health process feature engineering for broader applications can be a future direction.